Nexus Between Agriculture, Economy, Energy Use, and Ecological Footprint Toward Sustainable Development in Bangladesh - Rahman, Md. Shoaibur; Ridwan, Mohammad; Raihan, Asif; Khayruzzaman; Tanchangya, Tipon; Rahman, Junaid; Foisal, Md. Zia Uddin; Mohajan, Babla; Islam, Samanta (Journal of Environmental and Energy Economics, 2022)
The primary endeavor of this research is to empirically explore the implication of agriculture, economic growth, and energy usage on the ecosystem damage in Bangladesh from 1971 to 2022. In light of this, we tested the agriculture-induced environmental Kuznets curve (EKC) hypothesis incorporating ecological footprint (EF) rather than emissions because EF better illustrates environmental degradation. Our findings from the dynamic ordinary least squares (DOLS) estimation confirm the validity of the EKC framework for Bangladesh. Consequently, ecological damage intensifies with economic development and is enhanced by an elevated gross domestic product (GDP). Moreover, a boost in both the agricultural value added and power consumption upsurges EF. To put it another way, utilization of energy and crop production are significant factors that affect the state of the planet. Consequently, the government ought to formulate strategies that foster long-term prosperity by promoting renewable power usage and climate-smart agriculture.